Acute pharmacological inhibition of matrix metalloproteinase‐9 activity during development restores perineuronal net formation and normalizes auditory processing in Fmr1 KO mice. Issue 5 (8th June 2020) - Pirbhoy, Patricia S.; Rais, Maham; Lovelace, Jonathan W.; Woodard, Walker; Razak, Khaleel A.; Binder, Devin K.; Ethell, Iryna M.
Abstract: Individuals with Fragile X Syndrome (FXS) and autism spectrum disorder (ASD) exhibit cognitive impairments, social deficits, increased anxiety, and sensory hyperexcitability. Previously, we showed that elevated levels of matrix metalloproteinase‐9 (MMP‐9) may contribute to abnormal development of parvalbumin (PV) interneurons and perineuronal nets (PNNs) in the developing auditory cortex (AC) of Fmr1 knock‐out (KO) mice, which likely underlie auditory hypersensitivity. Thus, MMP‐9 may serve as a potential target for treatment of auditory hypersensitivity in FXS. Here, we used the MMP‐2/9 inhibitor, SB‐3CT, to pharmacologically inhibit MMP‐9 activity during a specific developmental period and to test whether inhibition of MMP‐9 activity reverses neural oscillation deficits and behavioral impairments by enhancing PNN formation around PV cells in Fmr1 KO mice. Electroencephalography (EEG) was used to measure resting state and sound‐evoked electrocortical activity in auditory and frontal cortices of postnatal day (P)22–23 male mice before and one‐day after treatment with SB‐3CT (25 mg/kg) or vehicle. At P27‐28, animal behaviors were tested to measure the effects of the treatment on anxiety and hyperactivity. Results show that acute inhibition of MMP‐9 activity improved evoked synchronization to auditory stimuli and ameliorated mouse behavioral deficits. MMP‐9 inhibition enhanced PNN formation, increased PV levels and TrkB phosphorylation yet reduced Akt phosphorylation in the AC of Fmr1 KO mice. Our results show that MMP‐9 inhibition during early postnatal development is beneficial in reducing some auditory processing deficits in the FXS mouse model and may serve as a candidate therapeutic for reversing sensory hypersensitivity in FXS and possibly other ASDs. Abstract : The current study uses the matrix metalloproteinase (MMP)‐2/9 inhibitor SB‐3CT to pharmacologically inhibit MMP‐9 activity postnatally and test if acute MMP‐9 inhibition reverses neural oscillation deficits, behavioral impairments, and enhances perineuronal net (PNN) formation around parvalbumin (PV) cells in Fmr1 KO mice. Results show improved evoked synchronization to auditory stimuli and mouse behavior, enhanced PNN formation and TrkB phosphorylation, and reduced aberrant Akt phosphorylation in the auditory cortex of Fmr1 KO mice. This suggests that MMP‐9 inhibition is beneficial in ameliorating cortical processing deficits in Fragile X Syndrome (FXS) and that MMP‐9 inhibitors may serve as therapeutic candidates to reduce sensory hypersensitivity.